Erodibility Estimation in some Soils of Tungabhadra and Vaigai Catchments. - Mukhi, A.K.; Gawande, S.P. (Journal of Soil and Water Conservation, 2022)
A comparison of relative suitability of soil properties, soil separates. erodibility indices and multivariable regression equations to predict relative soil erodibility was made on Tungabhadra and Vaigai catchment soil. The soil separates and erodibility indices were not suitable for already eroded areas. The soil pH was not suitable indicator for soil erodibility, whereas MEQ was quite suitable. The erosivity prediction ability of the soil separates varied and depended upon catchment, and the soil separates. The multivariable regression equationsideveloped were with low predictability inparticular for ER and D R The predictability washetter for Tungabhadra catchment soils than for Vaigai catchment soils. The soil separates, erodibility indices and M V RE were better for areas where erosional deposition has not taken place and is uniformfrom pedologic or geologic point of view.